Epistemic (In)justice as A Process to Decoding Digital Information from Law Perspective - Anugrah Anditya (Digital Press Social Sciences and Humanities)
In this digital era, information can be disseminated much easier due to the internet. Under openness principle of information on the internet, now we can access information relatively easily When those condition is viewed from Epistemic Justice theory as postulated by Miranda Fricker means we are going toward information justice since now almost every people can now contribute and access information, but the reality says not all those information on social media is the right information, some information can be categorized as mis-information some as dis-information. Based on those condition this research will then questioning relevancy between Epistemic Justice in this digital era with legal consequences in Information and Electronic Transactions Act. This is due to by implementing openness principle it means we can gain almost any information but also any person now can contribute to provide information for another internet user. With such conditions we must selective when choose who is our information provider since mis and dis information in law paradigm can have negative impact toward law subject, and can have legal consequences. Thats why we needs to rethink again, is from legal paradigm information justice is a good idea, or do we need to set back to epistemic injustice. The idea to use injustice practice is due to in law paradigm we must act carefully, and that’s why do we need to rethink again by being selective when we read digital information